Oral tributyrin prevents endotoxin-induced lipid metabolism disorder. Issue 2 (April 2015) - Miyoshi, Makoto; Iizuka, Norihito; Sakai, Shota; Fujiwara, Mayu; Aoyama-Ishikawa, Michiko; Maeshige, Noriaki; Hamada, Yasuhiro; Takahashi, Michiko; Usami, Makoto
Summary: Background & aims: Sepsis leads to dysregulation of lipid and lipoprotein metabolism. Butyrate increases peroxisome proliferator-activated receptors (PPARs), which are key nuclear hormone receptors to induce fatty acid oxidation and synthesis. Oral administration of tributyrin, a prodrug of butyrate contained in dairy products, suppresses lipopolysaccharide (LPS)-induced liver injury through attenuating nuclear factor-κB activity with an increased hepatoportal butyrate level. In this study, we elucidated the protective effect of oral administration of tributyrin against LPS-mediated lipid metabolism disorder in rats. Methods: Male Wistar rats were randomly divided and were administered tributyrin or vehicle orally 1 h before LPS injection and then sacrificed at 0, 1.5, 6, and 24 h after LPS. Liver tissue expressions of nuclear hormone receptors, enzymes associated with fatty acid metabolism, and histone acetylation were analyzed by real-time polymerase chain reaction or western blotting. Plasma lipids levels were measured. Results: Tributyrin enhanced expression of PPARs and histone H3 in the liver at basal levels. Tributyrin suppressed LPS-induced repression of PPARs fatty acid oxidation-associated enzymes: fatty acid transport protein and fatty acid binding protein, and fatty acid synthesis-associated enzyme: sterol regulatory element binding protein-1c. Tributyrin reduced the increase in plasma triglyceride, total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels at 24 h after LPS injection. Conclusions: Oral tributyrin administration prevented elevation of plasma triglyceride, TC, and LDL-C levels through improved fatty acid oxidation in endotoxemic rats.